Comparison of Respiratory Effects between Dexmedetomidine and Propofol Sedation for Ultrasound-Guided Radiofrequency Ablation of Hepatic Neoplasm: A Randomized Controlled Trial - Jeong, Heejoon (J Clin Med, 2021)
Patient’s cooperation and respiration is necessary in percutaneous radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC). We compared the respiratory patterns of dexmedetomidine and propofol sedation during this procedure. Participants were randomly allocated into two groups: the continuous infusions of dexmedetomidine-remifentanil (DR group) or the propofol-remifentanil (PR group). We measured the tidal volume for each patient’s respiration during one-minute intervals at five points and compared the standard deviation of the tidal volumes (SDvt) between the groups. Sixty-two patients completed the study. SDvt at 10 min was not different between the groups (DR group, 108.58 vs. PR group, 149.06, p = 0.451). However, SDvt and end-tidal carbon dioxide (EtCO(2)) level of PR group were significantly increased over time compared to DR group (p = 0.004, p = 0.021; ß = 0.14, ß = −0.91, respectively). Heart rate was significantly decreased during sedation in DR group (p < 0.001, ß = −2.32). Radiologist satisfaction was significantly higher, and the incidence of apnea was lower in DR group (p = 0.010, p = 0.009, respectively). Compared with propofol-remifentanil, sedation using dexmedetomidine-remifentanil provided a lower increase of the standard deviation of tidal volume and EtCO(2), and also showed less apnea during RFA of HCC.